MOTIVASI SANTRI DALAM MENGHAFAL AL-QUR’AN DI PONDOK TAHFIZ MESJID SYEKH HAJI JABANG TABIANG MELALUI METODE TASALSULI - Amelia Amelia; Darul Ilmi; Iswantir Iswantir; Arifmiboy Arifmiboy (KOLONI, 2022)
The background of this research is the students who memorize the Qur'an at Pondok Tahfiz Sheikh Haji Jabang Tabing Mosque, the motivation of children in memorizing is decreasing day by day, they are a lot of lazy in memorizing, many of their memorization is missing, there are still many who don't. serious in memorizing the Qur'an. This study uses a qualitative descriptive research method, namely research that tries to describe, describe and interpret a phenomenon that occurs in accordance with data that can be obtained in the field, which cannot be described in the form of numbers. This study describes the motivation of students in memorizing the Qur'an at Pondok Tahfiz Sheikh Haji Jabang Tabing Mosque through the Tasalsuli Method. In collecting the required data, the writer needs to do it through observation, interviews, informants, namely students, as key informants, tahfiz teachers and parents as supporting informants. The results showed that the lack of motivation in memorizing the Qur'an while internal factors (inside themselves) that influenced students in memorizing the Qur'an were seen from the physiological aspect, psychological aspects. 'an seen in the award or praise.  Keyword: Santri, Motivation in Memorizing the Qur'an